Development of an innovative flexible paper-based methanol fuel cell (PB-DMFC) sensing platform application to sarcosine detection - Carneiro, Liliana (2023)
This work describes for the first time a paper-based direct methanol fuel cell platform (PB-DMFC) that functions as an energy source and biosensor, assembled on a simple paper substrate for point-of-care (POC) applications, targeting sarcosine as proof-of-concept. Specifically, a methanol fuel cell strip was developed from a square of Whatman paper, acting as substrate. The paper strip was treated with an impermeable agent (paraffin solution) and supported all fuel cell device components, including the electrolyte (Nafion®), anode electrode (carbon black Pt/Ru), cathode electrode (carbon black Pt), and current collectors (silver edges). All the described components formed a flexible single layer that operated in a completely passive mode by adding few microliters of a methanol solution on the anode side and by using atmospheric oxygen on the cathode side. The obtained platform had a stable electrical signal with an average OCV value of 0.45-0.55V and a maximum power density of 20-50µW/cm2, depending on the methanol concentration used (0.5M 2M). A sensing layer was built in situ on the anode electrode by electropolymerization of a solution of 3,4-ethylenedioxythiophene (EDOT) and pyrrole (Py) as monomers. The obtained PB-DMFC/biosensor was calibrated at room temperature in buffer and healthy human urine and showed linear responses from 1.0×10-7 to 1.0×10-3M with a detection limit of 6.6×10-8M. Selectivity studies evidenced signals changing within 1-10%, both in positive and negative directions. Results evidenced good reproducibility. Overall, the obtained results demonstrate a self-sufficient biosensor for the detection of sarcosine consisting of an innovative paper-based methanol fuel cell strip. This concept can open new horizons for massification of biosensors even in places with energy shortage.